Getting started with MakerBot - Pettis, Bre; France, Anna Kaziunas; Shergill, Jay (Make: projects., 2013)
Ready to join the personal fabrication movement? This hands-on book shows you how to make a wide variety of physical objects with the amazing MakerBot 3D printer. It's handy when you need a replacement for something lost, broken, or no longer made-like a knob on your stove. You can make things instead of buying them, or solve problems with inventions of your own. The possibilities are endless, and MakerBot is the fun, affordable, and inspiring way to go. Get started with your own little factory today! Set up your MakerBot Replicator 2 and understand how it worksLearn the basics and print 10.